ENGLISH LEARNING EDUCATIONAL GAMES FOR HEARING AND SPEECH IMPAIRMENT STUDENTS AT SLB B YAKUT PURWOKERTO - Yogiek Indra Kurniawan; Uki Hares Yulianti; Nadia Gitya Yulianita; Andika Putra Pratama (Informatika, Universitas Jenderal Soedirman, 2022)
Students with hearing and speech impairment at the Special School for the Hearing and Speech Impairment (SLB B) Yakut Purwokerto do not have high level of interest in learning. Moreover, the use of manual learning media which are based on books and blackboards also causes a lack of students’ understanding. This research aims to develop an alternative learning media which are based on educational games to learn English for students with hearing and speech impairment at SLB-B Yakut Purwokerto with the name